Legionella effector MavC targets the Ube2N~Ub conjugate for noncanonical ubiquitination - Kedar Puvar (Nature Portfolio, 2020)
The Legionella pneumophila effector MavC inhibits the human ubiquitin-conjugating enzyme Ube2N. Here, the authors combine NMR, X-ray crystallography and biochemical assays and show that MavC catalyses the intramolecular transglutaminase reaction between the Ube2N and Ub subunits of the Ube2N∼Ub conjugate and present the substrate- and product-bound MavC crystal structures.